2002
DOI: 10.1056/nejm200201103460218
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Proton-Pump Inhibitor for Metabolic Disturbances Associated with Anorexia Nervosa

Abstract: Our fax numbers: 617-739-9864 and 617-734-4457Our e-mail address: letters@nejm.orgWe cannot acknowledge receipt of your letter, but we will notify you when we have made a decision about publication. We are unable to provide prepublication proofs. Financial associations or other possible conflicts of interest must be disclosed. Submission of a letter constitutes permission for the Massachusetts Medical Society, its licensees, and its assignees to use it in the Journal' s various print and electronic publication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…These acute medications may be prescribed to treat sexually transmitted infections (eg, azithromycin) or gastrointestinal symptoms (eg, ondansetron, omeprazole) from eating disorders. 27,28 Some are also available over-the-counter (OTC), specifically NSAIDs and PPIs. Product labeling for OTC medications does not always include comprehensive information on adverse effects, including DDIs.…”
Section: Figurementioning
confidence: 99%
“…These acute medications may be prescribed to treat sexually transmitted infections (eg, azithromycin) or gastrointestinal symptoms (eg, ondansetron, omeprazole) from eating disorders. 27,28 Some are also available over-the-counter (OTC), specifically NSAIDs and PPIs. Product labeling for OTC medications does not always include comprehensive information on adverse effects, including DDIs.…”
Section: Figurementioning
confidence: 99%
“…For those patients who vomit and in whom normokalaemia cannot be maintained with oral supplementation, the use of a proton pump inhibitor (PPI) may be a useful second-line treatment. 9,10 By reducing the secretion of gastric acid, these drugs minimize the loss of hydrogen ions in the vomit and the consequent alkalosis, and thereby reduce the compensatory renal excretion of potassium. It has been argued that PPIs will be ineffective unless sodium depletion is also corrected, 6 but it is uncertain whether sodium depletion is a significant factor in all patients and whether volume replacement is always required; 9 these questions need to be addressed in a randomized controlled trial.…”
Section: Electrolyte Disturbancesmentioning
confidence: 99%
“…In 2002 Eiro, Katoh, and Watanabe described using a PPI to treat persistent hypokalemia and metabolic alkalosis in a female patient with anorexia nervosa and a history of self-induced vomiting. 6 Potassium levels improved after treatment with lansoprazole at a dose of 15 mg per day, and remained normal for one year of follow-up despite persistence of self-induced vomiting. 6 No other case reports or higher-quality studies were found on the use of PPIs in the treatment of hypokalemia in eating disorder patients.…”
Section: Casementioning
confidence: 91%
“…6 Potassium levels improved after treatment with lansoprazole at a dose of 15 mg per day, and remained normal for one year of follow-up despite persistence of self-induced vomiting. 6 No other case reports or higher-quality studies were found on the use of PPIs in the treatment of hypokalemia in eating disorder patients. The mechanism through which pantoprazole corrected hypokalemia in this case can be inferred from the pathophysiology of hypokalemia in persistent vomiting.…”
Section: Casementioning
confidence: 91%
See 1 more Smart Citation